KAMPUS MERDEKA (INDEPENDENT CAMPUS) POLICY IN INDONESIA: A BRIEF OVERVIEW - Etik Umiyati; Eristian Wibisono (Balai Besar Guru Penggerak Jawa Timur, 2023)
Implementing the Kampus Merdeka (Independent Campus) policy for higher education in Indonesia opens new perspectives on the transformation of higher education. This strategic approach aims to improve institutions' quality flexibly and wants to place students in a central position in the university by involving students in the real-world activities through various field projects. Nevertheless, few doubts arise on how this policy program is implemented, including its sustainability. Through evidence-based critical review, this article aims to review the implementation of the Kampus Merdeka policy and some of the challenges that may arise. We identify three main challenges, including decision-making authority, external collaboration, and benchmarks of success which then lead to conclusions and recommendations regarding the skills of higher education institutions in carrying out external collaboration and tools to measure the success of field projects.AbstrakPenerapan kebijakan Kampus Merdeka pada pendidikan tinggi di Indonesia membuka perspektif baru dalam transformasi pendidikan tinggi. Pendekatan strategis ini bertujuan untuk meningkatkan kualitas institusi secara fleksibel dan menempatkan mahasiswa pada posisi sentral di perguruan tinggi dengan melibatkan mahasiswa dalam kegiatan di dunia nyata melalui berbagai proyek lapangan. Namun demikian, beberapa keraguan muncul tentang bagaimana program kebijakan ini diimplementasikan, termasuk keberlanjutannya. Dengan pendekatan tinjauan literatur berbasis bukti, artikel ini mengulas implementasi kebijakan Kampus Merdeka dan beberapa tantangan yang mungkin muncul. Kami mengidentifikasi tiga tantangan utama, antara lain kewenangan pengambilan keputusan, kolaborasi eksternal, dan tolok ukur keberhasilan. Ketiganya mengarah pada kesimpulan dan rekomendasi mengenai keterampilan institusi pendidikan tinggi dalam melakukan kolaborasi eksternal beserta instrumen untuk mengukur keberhasilan proyek-proyek di lapangan.